Inovasi Pembelajaran Anak Usia Dini Melalui Media Kincir Ria Matematika di TK At-Tien Sumber Gayam Pamekasan - Ummi Aisyatus Salehah Ahlul Jannah; Mutiatul Hasanah; Imelyatun Namilah; M. Riqi Firmansyah; Ismail Makki (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The lack of interest of young children in learning numbers is a common challenge in kindergarten learning activities. Children tend to be passive during the mathematics learning process because the approach used is not appropriate to their age developmental characteristics, which prefer play, movement, and direct interaction with concrete media. To address this problem, the Community Service Program (KKN) at At-Tien Kindergarten, Sumber Gayam, focused on learning innovation by designing a simple media called the Mathematics Ferris Wheel. This media was designed by combining elements of play and motor activity, making it more engaging for children. The research in this community service activity used a Participatory Action Research (PAR) approach, which actively involved teachers and students in the planning, implementation, and evaluation stages. The media was implemented by children turning the Ferris wheel in turns, then calling out the number indicated along with the numbers before and after. Through this activity, children not only learned to recognize number sequences but also practiced concentration, courage, and communication skills. The implementation results showed that the use of the Mathematics Ferris Wheel was able to significantly improve the understanding of number concepts in early childhood. Furthermore, children's active involvement in learning also increased, demonstrated by their enthusiasm in participating in the game from start to finish. Teachers found this media to be highly beneficial because it is easy to use, flexible, and adaptable to teach other topics such as colors, shapes, and letters. Thus, this KKN activity demonstrates that innovative, participatory learning media can create a fun, contextual, and effective learning environment. Such efforts are a practical solution to improving the quality of learning in early childhood education